The Effect of Using E-Module Based on Flipbook Maker on Student Understanding of the Starter System - Suprayogi, Sidiq; Sutopo, Yeri; Priyatna, Bambang Sugeng; Anis, Samsudin (Universitas Negeri Semarang, 2024)
A significant challenge in contemporary education is the limited understanding of technical subjects by students, such as the starter system within the Automotive Engineering program. The use of less engaging learning media leads to a decrease in student motivation, which ultimately affects academic performance. This study investigates the impact of an e-module, designed with Flipbook Maker, on student comprehension of the starter system. A quantitative approach was employed, utilizing pretests and posttests, along with surveys distributed to measure changes in understanding and student responses to digital learning media. The collected data was analyzed using simple linear regression through the SPSS software. The study involved a sample of 70 students from the XI grade of the Automotive Engineering program at SMK Negeri 1 Kandeman. The results revealed that the use of the e-module significantly improved student understanding, with a correlation coefficient (R) of 0.469 and an effect size (R Square) of 0.673, indicating that 67.3% of the variance in understanding was explained by the e-module. In conclusion, the e-module effectively enhanced student comprehension of the starter system. Students expressed a preference for digital learning media due to its flexibility in being accessed anytime and anywhere, both online and offline.